2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333704
|View full text |Cite
|
Sign up to set email alerts
|

Human motor cortical activity recorded with Micro-ECoG electrodes, during individual finger movements

Abstract: In this study human motor cortical activity was recorded with a customized micro-ECoG grid during individual finger movements. The quality of the recorded neural signals was characterized in the frequency domain from three different perspectives: (1) coherence between neural signals recorded from different electrodes, (2) modulation of neural signals by finger movement, and (3) accuracy of finger movement decoding. It was found that, for the high frequency band (60–120 Hz), coherence between neighboring micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 14 publications
7
118
1
1
Order By: Relevance
“…These changes in low and high frequency bands are in agreement with previous MEG (Waldert et al 2008) and ECoG studies (Leuthardt et al 2004;K. J. Miller et al 2007;Wang et al 2009). In addition, Wang et al (Wang, Sudre, et al 2010) demonstrated that high-gamma band activity captured by MEG showed directional modulation similar to what was observed previously using invasive recordings in humans (ECoG) (Leuthardt et al 2004) and non-human primates (local field potentials) (Heldman et al 2006) and has been used for BMI control.…”
Section: Meg For Bmi Technology Research and Developmentsupporting
confidence: 81%
See 1 more Smart Citation
“…These changes in low and high frequency bands are in agreement with previous MEG (Waldert et al 2008) and ECoG studies (Leuthardt et al 2004;K. J. Miller et al 2007;Wang et al 2009). In addition, Wang et al (Wang, Sudre, et al 2010) demonstrated that high-gamma band activity captured by MEG showed directional modulation similar to what was observed previously using invasive recordings in humans (ECoG) (Leuthardt et al 2004) and non-human primates (local field potentials) (Heldman et al 2006) and has been used for BMI control.…”
Section: Meg For Bmi Technology Research and Developmentsupporting
confidence: 81%
“…Also, implantable electrode arrays typically cover only a small cortical area making accurate pre-surgical localization of the targeted implantation site critical. For example, intracortical microelectrode arrays typically cover only a small area of cortex (4×4mm 2 (Hochberg et al 2006)) and high density ECoG grids (Wang et al 2009) may cover an area only slightly larger (15×15mm 2 ). Another direct role for rtMEG is in pre-surgical training of patients who are scheduled to have electrodes implanted for BMI applications.…”
Section: Meg For Bmi Technology Research and Developmentmentioning
confidence: 99%
“…DFA has been shown to give optimal results when the sample sizes are on the order of 50 or less per condition (25). The manner in which DFA was applied in this work was closely related to linear discriminant analysis (LDA), which has recently been applied to classifying ECoG data based on spectral response (26). On high-dimensional data, a principal component analysis (PCA) decomposition gives a low-dimensional representation of the time series data, and it is common to use DFA in this lowdimensional space.…”
Section: Methodsmentioning
confidence: 99%
“…Even with these barriers investigators have achieved multiple degree of freedom control in non-human primate studies and in human studies. 20,21 It seems likely that higher degrees of motor control will be achieved in humans in the next 10 years and that a clinically viable product will be available. Creating a stable interface will likely still be the subject of investigation for electrodes that penetrate the brain.…”
Section: Direct Brain Interfacesmentioning
confidence: 99%